Digital Visual Branding : Membangun Tata Kelola Manajemen Digital Branding Desa Gisik Cemandi - Gina Amara Amodia; Sahrul Rizkyanto; Hanan Salsabila; Triyoga Agung Laksana; Jokhanan Kristiyono; Aulia Afniar Rahmawati; E. Rizky Wulandari (Prapanca : Jurnal Abdimas, 2024)
Gisik Cemandi Sedati refers to an area or village in East Java, Indonesia, which is known for its tourism potential, especially related to beaches and sea-related activities. This area has the potential for natural tourism, especially beach tourism, because it is located on the northern coast of Java. The people of Gisik Cemandi Village generally work as salt farmers, fishermen, and small traders. Most of the population has not made full use of digital technology, especially in the context of tourism marketing and promotion. This research focuses on the implementation of digital branding for Gisik Cemandi Village, Sedati, Sidoarjo through the Abdimas (Community Service) program by Stikosa-AWS. This service began with the lack of digital exposure in Gisik Cemandi Village, which has significant tourism potential. The main goal is to increase the visibility and branding of the village through digital strategies, so that it can attract more tourists and improve the local economy. The methods used include SWOT analysis to identify strengths, weaknesses, opportunities, and threats in village digital marketing. Furthermore, a digital content strategy involving websites, social media, and online campaigns was developed. The Abdimas Stikosa-AWS program also involves training villagers in managing digital content. The results of this program include a significant increase in online traffic to the village's digital platform, increased interaction on social media, and an increase in the number of tourist visits. This research confirms that the implementation of digital branding through the Abdimas program can be effective in increasing the visibility and attractiveness of village tourism.